2020
DOI: 10.1101/2020.04.23.055285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symbiotic and non-symbiotic members of the genusEnsifer(syn.Sinorhizobium) are separated into two clades based on comparative genomics and high-throughput phenotyping

Abstract: symbiotic members of the genus Ensifer (syn. Sinorhizobium) are 1 separated into two clades based on comparative genomics and high-throughput phenotyping 2 3

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…The ability of bacteria to grow in LB broth medium at 30°C was assessed using 96-well microplates as detailed by Fagorzi et al (2020). Growth was estimated (over a 48 h period) on the basis of optical density (595 nm) by taking readings at hourly intervals using a FLUOstar OPTIMA plate reader (BMG LABTECH, Germany).…”
Section: Phenotypic Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of bacteria to grow in LB broth medium at 30°C was assessed using 96-well microplates as detailed by Fagorzi et al (2020). Growth was estimated (over a 48 h period) on the basis of optical density (595 nm) by taking readings at hourly intervals using a FLUOstar OPTIMA plate reader (BMG LABTECH, Germany).…”
Section: Phenotypic Characterizationmentioning
confidence: 99%
“…The genus Ensifer consists of diverse species of soil bacteria and includes bacterial predators and agriculturally important species capable of fixing nitrogen in symbiotic association with legume plants such as alfalfa (Medicago sativa). This bacterial genus is currently divided into two major clades based on phylogenetic analysis of multiple housekeeping (core) genes (Martens et al, 2008;Kumar et al, 2017;Fagorzi et al, 2020;Kuzmanović et al, 2022). One of these clades is represented by the non-symbiotic species, Ensifer morelensis (Wang et al, 2002) and the predatory species, Ensifer adhaerens (Casida, 1982), and the other clade by symbiotic nitrogen fixing species such as Ensifer meliloti (de Lajudie et al, 1994) and Ensifer medicae (Rome et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In the most recent studies about the nonsymbiotic Ensifer and symbiotic Sinorhizobium , Fagorzi et al . (2020) suggested that the currently combined genus Ensifer should be divided back into pre‐existing of two genera, based on their distinct genomic and phenotypic properties and large segregation in two phylogenetically distinct clades.…”
Section: Alpha‐rhizobia (α‐Rhizobia)mentioning
confidence: 99%
“…7.1. Based on an extensive genomic and phenotypic analysis of the genus Ensifer / Sinorhizobium , Fagorzi et al [ 10 ] concluded that it is made of two distinct clades, with inter-clade genomic similarity under 85 % average nucleotide identity (ANI) and 90 % average amino acid identity (AAI). They presented a large body of biological evidence suggesting that these clades harbour significantly different organisms, with one containing symbiotic strains and the other non-symbiotic strains.…”
Section: Minute 7 Recent Relevant Publications In Genome-based Taxonomymentioning
confidence: 99%